Antifungal effects of cold plasma, coupled with modified atmosphere packaging on asparagus during cold storage - Wang, Li-Xia; Choi, In-Lee; Kang, Ho-Min (Penerbit Universiti Kebangsaan Malaysia, 2021)
Asparagus spear is vulnerable to microbial groups which can cause deterioration and short shelf-life after harvesting. The effects of cold plasma, coupled with modified atmosphere (MA) packaging on microorganism development, and quality changes of green asparagus were investigated. The development of microorganisms was inhibited after sterilisation. After 21 days of storage, cold plasma for 6 h (P6h) and hot water combined with cold plasma for 3 h (HW+P3h) treatments obtained the lowest number of aerobic bacteria. Hot water (HW), P6h and HW+P3h treatments showed higher inhibition effect on yeast and mold, and also on E. coli. Visual quality and off-odour of P6h treatment were superior to and inferior to other treatments, respectively. Hot water and cold plasma treatments alone inhibited the firming. Cold plasma 1 (P1h) and 3 h (P3h) were better in retarding yellowing of asparagus. A difference in electrolyte leakage (EL) between control (43%) and sterilisation treatments (greater than 60%) was immediately observed on the sterilisation day. Treatments using HW and P1h decreased the EL after 21 days. The soluble solid content (SSC) decreased based on the initial content, and hot water treatment resulted in higher SSC. Increases in ethylene (C₂H₄) and carbon dioxide production and decrease in oxygen were observed during the first 3 days. The content of C₂H₄ under cold plasma treatments was higher than hot water and control on day 21. These results suggested that cold plasma 6 h treatment resulted in better sensory quality and less decay and softening for green asparagus.